ผลของน้ำหมักชีวภาพจากของเหลือทิ้งโรงงานอุตสาหกรรมปลาป่นต่อการเจริญเติบโตและผลผลิตของผักกาดหอมห่อและดาวเรือง - ขณะรัตน์ อารีรัตน์; ตังคณานุรักษ์ คณิตา; ตั้งกุลบริบูรณ์ รจนา; พิริยะภัทรกิจ อนันต์ (Thai Journal of Science and Technology, 2019)
Abstract This study aimed to utilize waste of fish meal factory by converting waste into bioextract for plant. The recipe of making bioextract of major waste such as fish blood and bones together with other materials, molasse and lactic acid bacteria (LAB) was figured out. The trials revealed that the proper ratio of fish blood: fish bones: molasse: LAB suspension to obtain best quality of bioextract regarding its plant nutrients was 15 kg: 1 kg: 5 L: 0.2 L. The fermentation was done in plastic container with daily agitation for 21 days. The obtained emulsion contained 1.08-1.73-2.04 % of N-P-K, and 0.21, 0.19 and 0.14 mg/L of Mg, Ca and S that could be used as foliar fertilizer with 1 : 150 of dilution for leafy vegetable such as head lettuce. The growth promotion of lettuce by the fish waste bioextract was better than commercial fish emulsion providing 91.68 g FW of lettuce, while the commercial one was 81.39 g FW. Additionally, once the fish waste bioextract was brought to formulate as chemical organic fertilizer of 3-3-3 and used as side dressing fertilizer for marigold comparing with recommended chemical fertilizer application. The results turned out that there was no significant difference in terms of flower quantity and quality per plant. Flower diameter of 6.56 cm, 4.33 flowers/plant obtained when the marigold was applied with chemical organic fertilizer 3-3-3 from fish waste, while the diameter of 6.71 cm, 4.67 flowers/plant obtained from the marigold with recommended chemical fertilizer application. Keywords: bioextract; waste; fishmeal factory